Pengaruh Kepadatan Berbeda Terhadap Kinerja Produksi dan Kualitas Air Ikan Patin (Pangasius Hypophthalmus) Pada Media Bersalinitas 4 ppt - Nurussalam, Wildan; Supriyono, Eddy; Ayuningtyas, Lintang Sekar; Mahmud, Moh Burhanuddin (Jurnal Akuakultur Sungai dan Danau, 2026)
The use of isoosmotic media has been recommended as one of the efforts to reduce stress in fish kept in high stocking densities. Increases in stocking density should consider carrying capacity and water quality. One of the water quality parameters that can support the survival of catfish is maintenance in an isoosmotic condition with a salinity of 4 ppt. This study aims to analyze the effects of different densities on production performance, water quality, and physiological responses of Siamese catfish (Pangasius hypophthalmus) in media with a salinity of 4 ppt. The research was conducted using a completely randomized design with four density treatments (5 fish L-1, 8 fish L-1, 11 fish L-1, and 14 fish L-1) and three replications for each treatment. The results show that salinity of 4 ppt can support the life of catfish up to high densities with the best production performance at a stocking density of 14 fish L-1.